As ressonâncias do poder em Observações sobre o direito de punir e Mineirinho de Clarice Lispector - Yokoyama, Adriana (2017)
The study aims to approach the power relations in Clarice Lispector‘s two narratives: Observações sobre o direito de punir and Mineirinho. Aiming to reform the Brazilian prison system, Clarice writes about the need for a "duty to punish" in order to restore life into normality. In Mineirinho, the writer, immersed in a sense of compassion, feels the death of a criminal killed by thirteen shots by Rio police, wondering about the forms of penalties legitimated by the state and the reproduction of their violence. In this way this research is the result of the awareness that Clarice's work is able to allude to the creation of perspectives, related to understanding and recognition of the human condition. The disruptive effect of her writing, which transcends the enunciation and allows the reader a survey of experiences, in which are yours or from the "others", is observed from the deepening works. In this context, this analysis will be conducted by the studies about violence, memory, and identity, supporting this political and authoritarian bias represented by the state, as well as a brief overview of the relationship between fiction and reality interrelated in her works.